Rickettsia felis in Fleas, Germany - Jeremie Gilles; Frank Thomas Just; Cornelia Silaghi; Ingrid Pradel; Lygia Maria Friche Passos; Heidi Lengauer; Klaus Hellmann; Kurt Pfister (Emerging Infectious Diseases, 2008)
Among 310 fleas collected from dogs and cats in Germany, Rickettsia felis was detected in all specimens (34) of Archaeopsylla erinacei (hedgehog flea) and in 9% (24/226) of Ctenocephalides felis felis (cat flea). R. helvetica was detected in 1 Ceratophyllus gallinae (hen flea).